Heinrich Schenker's conception of harmony - Wason, Robert W. 1945-; Brown, Matthew 1957- (Eastman studies in music, 2020)
The first detailed study of Schenker's pathbreaking 1906 treatise, showing how it reflected 2500 years of thinking about harmony and presented a vigorous reaction to Austro-Germanic music theory ca. 1900